2017
DOI: 10.3389/fmicb.2017.01230
|View full text |Cite
|
Sign up to set email alerts
|

Extensively Drug-Resistant Klebsiella pneumoniae Causing Nosocomial Bloodstream Infections in China: Molecular Investigation of Antibiotic Resistance Determinants, Informing Therapy, and Clinical Outcomes

Abstract: The rise in diversity of antimicrobial resistance phenotypes seen in Klebsiella pneumoniae is becoming a serious antibiotic management problem. We sought to investigate the molecular characteristics and clinical implications of extensively drug-resistant (XDR) K. pneumoniae isolated from different nosocomial bloodstream infections (BSIs) patients from July 2013 to November 2015. Even in combination treatment, meropenem did not protect against mortality of BSIs patients (P = 0.015). In contrast, tigecycline in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 61 publications
5
44
1
1
Order By: Relevance
“…Unfortunately, these types of antibiotics possess severe adverse effects, which blocked substantial clinical applications. From this study, for carbapenems, the susceptibility was 83.6%, and despite the low ratio of CRE (16.4%), it can result in extremely grievous consequences [15]. Depending on the present study, antibiotic prophylaxis and empirical are routine manipulation during the neurosurgery operation.…”
Section: Discussionmentioning
confidence: 69%
“…Unfortunately, these types of antibiotics possess severe adverse effects, which blocked substantial clinical applications. From this study, for carbapenems, the susceptibility was 83.6%, and despite the low ratio of CRE (16.4%), it can result in extremely grievous consequences [15]. Depending on the present study, antibiotic prophylaxis and empirical are routine manipulation during the neurosurgery operation.…”
Section: Discussionmentioning
confidence: 69%
“…Selection of spontaneous glyphosate-resistant and generation of aroA catalytically active-site glyphosate-resistant mutants in K. pneumoniae. As K. pneumoniae rapidly acquires resistance to antibiotics (28,29), we evaluated the rate of spontaneous glyphosate resistance of K. pneumoniae (see Materials and Methods). WT K. pneumoniae was grown overnight in L and plated on M9ϩglucose containing 1,000 g/ml glyphosate, 50 g/ml rifampin (RIF), or 200 g/ml streptomycin (STR).…”
mentioning
confidence: 99%
“…Wenzi Bi. et al, in 2017, reported the dissemination and epidemicity of clinical XDR K. pneumoniae strains result from horizontal transmission of multiple resistance determinants via IncF plasmids [67]. More so, the multi replicon nature of the p18-43_01 plasmid was not peculiar, as a diversity of plasmid incompatibility groups (Inc), including IncX, IncR, IncN, IncL/M, IncA/C, and IncF have been linked with NDM variants [26,27,68,69].…”
Section: Discussionmentioning
confidence: 99%